Geomechanical Influence On Rock Mass Deformation At Hulu Terengganu Hydroelectric Power Surge Chamber Cavern - Mochamad, Trisugiwo (2017)
The Surge Chamber Cavern (SCC) as part of underground power station in Hulu Terengganu Hydro Electric Project (HEP) is provided to protect the tailrace tunnel from water hammer effect due to fluctuation of water. The SCC is located is located downstream of the powerhouse and discharges in to a single inclined long tailrace tunnel under pressure. The SCC has D shape with dimension of 14 m span, 46 m high, 65 m length and constructed 200 m under surface. The problem statements are the SCC was excavated in jointed volcanic rock formation, homogeneous isotropic, and has stressed; presence of “buckling” at middle section of long walls; some geological overbreaks and the cavern has constructed without concrete support (unlined).The objective this study are characterised of rock, mechanical properties, insitustress condition of rock mass; analyse the effect of rock mass properties due to the deformation and to compare between the numerical analysis and monitoring data due to deformation of SCC. The data collected on site were used to analysis Dip, Unwedge and Phase2 software for numerical analysis and analysing of displacement monitoring.From this study, it was concluded that rock mass of SCC classified as a good rock however it was deformed, it was visualized on site as buckling, some overbreak/collapse and creep, the maximum displacement 26.45 mm on the middle of long-wall. The peak displacement had been happened during excavation period and observing shows the displacement is still continuing as creep, ≤0.05 mm/ month.